Derivation of a bidomain model for bundles of myelinated axons. (April 2023) - Jerez-Hanckes, Carlos; Martínez Ávila, Isabel A.; Pettersson, Irina; Rybalko, Volodymyr
Abstract: The work concerns the multiscale modeling of a nerve fascicle of myelinated axons. We present a rigorous derivation of a macroscopic bidomain model describing the behavior of the electric potential in the fascicle based on the FitzHugh–Nagumo membrane dynamics. The approach is based on the two-scale convergence machinery combined with the method of monotone operators.